Thermal barrier ceramic material, preparation method thereof and thermal barrier coating material
By preparing the thermal barrier ceramic material composed of xA2O3·yBO2·zZrO2, the problem of insufficient fracture toughness and phase stability of existing materials is solved, and the thermal barrier ceramic material with high fracture toughness and phase stability is achieved, which extends its service life at high temperatures.
Patent Information
- Application Number
- CN202311360749.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-19
- Publication Date
- 2025-04-22
AI Technical Summary
The existing thermal barrier coating materials have low fracture toughness and phase stability, which leads to a short service life at high temperatures and is difficult to meet the technical needs of long life.
By preparing a new thermal barrier ceramic material, it adopts the composition of xA2O3·yBO2·zZrO2, where A is a trivalent rare earth metal ion, B is a tetravalent rare earth metal ion, the value range of x is 5% to 8%, and the value range of y is 0% to 70%, so as to ensure that the material has a stable cubic phase and a partial tetragonal phase, and improve its fracture toughness and phase stability.
The high fracture toughness (KIC ≥ 2.8Mpam1/2) and phase stability of thermal barrier ceramic materials are achieved, which extends its service life at high temperatures, and has the advantages of high melting point, low thermal conductivity and high thermal expansion coefficient.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure HDA0004506635720000011
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of thermal barrier ceramic materials, and in particular to a thermal barrier ceramic material and a preparation method thereof, and a thermal barrier coating material. Background Art
[0002] Thermal barrier coating is a ceramic coating that is deposited on the surface of a substrate material such as a high-temperature metal or superalloy to protect the substrate material so that devices made of it, such as engine turbine blades, can operate at high temperatures. The application of thermal barrier coatings can not only improve the substrate's ability to resist high-temperature corrosion and further increase the engine's operating temperature, but also reduce fuel consumption, improve efficiency, and extend the service life of hot end components.
[0003] A lot of research has focused on finding new thermal barrier coating materials with low thermal conductivity. However, whether it is rare earth zirconate or other new thermal barrier coating materials, their fracture toughness and phase stability are very low, which seriously reduces the thermal cycle life of the coating. Therefore, finding thermal barrier coating materials with high fracture toughness and high phase stability has become the key to obtaining new thermal barrier coating technology with long life. Summary of the invention
[0004] The embodiments of the present application provide a thermal barrier ceramic material and a preparation method thereof, and a thermal barrier coating material, which can improve the phase stability and fracture toughness of the thermal barrier ceramic, and at the same time have the advantages of high melting point, low thermal conductivity and high thermal expansion coefficient.
[0005] In the first aspect, an embodiment of the present application provides a thermal barrier ceramic material, which has the following composition: xA2O3·yBO2·zZrO2; wherein A is a trivalent rare earth metal ion; B is a tetravalent rare earth metal ion; the value range of x is 5% to 8%; the value range of y is 0% to 70%; 2x+y+z=1; the thermal barrier ceramic material includes a cubic phase structure.
[0006] According to an embodiment of the first aspect of the present application, A includes Yb 3+ 、Lu 3+ Sc 3+ 、Nd 3+ 、Eu 3+ 、Sm 3+ , Gd 3+ 、Ho 3+ 、Dy 3 + , Y 3+ 、Tm 3+ , Er 3+ At least one of; B includes Ce 4+ and Hf 4+ At least one of .
[0007] According to an embodiment of the first aspect of the present application, A includes a first type of trivalent rare earth metal ions and a second type of trivalent rare earth metal ions. Based on the total amount of A, the content of the first type of trivalent rare earth metal ions is 60% to 100%, and the content of the second type of trivalent rare earth metal ions is 0% to 40%; the first type of trivalent rare earth metal ions include Yb 3+ 、Lu 3+ Sc 3+ , Er 3+ At least one of the second trivalent rare earth metal ions including Nd 3+ 、Eu 3+ 、Sm 3+ , Gd 3+ 、Ho 3+ 、Dy 3+ , Y 3+ 、Tm 3+ At least one of .
[0008] According to an embodiment of the first aspect of the present application, B includes 0-20 mol% of Ce 4+ and 0-50 mol% Hf 4+ .
[0009] According to an embodiment of the first aspect of the present application, based on the total amount of the phase structure as 100%, the content of the cubic phase structure is 60%-100%.
[0010] According to an embodiment of the first aspect of the present application, the thermal barrier ceramic material further includes a tetragonal phase and a monoclinic phase, and the content of the monoclinic phase is 0-3% based on the total amount of the phase structure as 100%.
[0011] According to the embodiment of the first aspect of the present application, the fracture toughness K IC ≥2.8Mpam 1 / 2 .
[0012] In a second aspect, an embodiment of the present application provides a method for preparing a thermal barrier ceramic material, which is used for the thermal barrier ceramic material of the present application, and is characterized by comprising:
[0013] Providing raw material components, including xA2O3, yBO2 and zZrO2, x is in the range of 5% to 8%; y is in the range of 0 to 70%; 2x+y+z=1; wherein A is a trivalent rare earth metal ion; B is a tetravalent rare earth metal ion;
[0014] mixing the raw material components to obtain a precursor mixture;
[0015] ball milling the precursor mixture and the solvent to obtain a mixed slurry;
[0016] The mixed slurry is subjected to solid-liquid separation to obtain a bulk material, and the bulk material is pre-calcined at least once to obtain a pre-fired thermal barrier ceramic material;
[0017] The pre-fired thermal barrier ceramic material is ball-milled, sieved, pre-pressed, and then calcined at 1350° C.-1600° C. for 6 h-10 h to obtain the thermal barrier ceramic material.
[0018] According to an embodiment of the second aspect of the present application, A includes Yb 3+ 、Lu 3+ Sc 3+ 、Nd 3+ 、Eu 3+ 、Sm 3+ , Gd 3+ 、Ho 3+ 、Dy 3 + , Y 3+ 、Tm 3+ , Er 3+ At least one of .
[0019] According to an embodiment of the second aspect of the present application, B includes Ce 4+ and Hf 4+ At least one of .
[0020] In a third aspect, an embodiment of the present application provides a thermal barrier coating material, characterized in that it is formed by granulating and spraying the thermal barrier ceramic material of the present application.
[0021] Compared with the prior art, this application has at least the following beneficial effects:
[0022] The thermal barrier ceramic material in the present application is based on ZrO2. By adjusting the total amount and type of rare earth doping elements, the thermal barrier ceramic material has a stable cubic phase and a partial tetragonal phase, and improves the phase stability while ensuring that the material has high fracture toughness and low thermal conductivity. Among them, based on the total amount of the substance as 100%, the doping amount of trivalent rare earth metal ion oxide A2O3 in the thermal barrier ceramic material is 5%-8%, so that the thermal barrier ceramic material is mainly in a cubic phase, and improves the phase stability while ensuring that the material has high fracture toughness and low thermal conductivity. The doping amount of tetravalent rare earth metal ion B is 0%-70%, and the tetravalent rare earth metal ion B and the oxide formed by it may exist or not. When the tetravalent rare earth metal ion exists, the formed BO2 is similar to the ZrO2 lattice structure, which can further improve the phase stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without paying creative work.
[0024] Figure 1 The X-ray diffraction patterns of the thermal barrier ceramic materials prepared in Examples 1 to 4 before and after calcination at 1400° C. for 100 h; (a) is before heat treatment, and (b) is after heat treatment; t: tetragonal phase; c: cubic phase. DETAILED DESCRIPTION
[0025] In order to make the application purpose, technical solution and beneficial technical effect of the present application clearer, the present application is further described in detail in conjunction with the embodiments below. It should be understood that the embodiments described in this specification are only for explaining the present application, not for limiting the present application.
[0026] For simplicity, this application only explicitly discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unclearly recorded range; and any lower limit can be combined with other lower limits to form an unclearly recorded range, and any upper limit can be combined with any other upper limit to form an unclearly recorded range. In addition, although not clearly recorded, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unclearly recorded range.
[0027] In the description of the present application, it should be noted that, unless otherwise specified, “above” and “below” are inclusive of the number, and the “multiple” in “one or more” means two or more than two.
[0028] The above application content of the present application is not intended to describe each disclosed embodiment or each implementation in the present application. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided by a series of examples, which can be used in various combinations. In each example, enumeration is only used as a representative group and should not be interpreted as exhaustive.
[0029] Traditional YSZ materials have poor phase stability. When used for a long time at 1300℃, phase change may occur, resulting in degradation of coating performance and a significant reduction in thermal cycle life. The newly developed advanced rare earth zirconate (RE2Zr2O7) series materials have excellent phase stability and low thermal conductivity. However, their fracture toughness is very low, resulting in a very low lifespan when used as a thermal barrier material.
[0030] In view of the above problems, the embodiments of the present application are based on zirconium oxide, and change the doping type and total amount of rare earth doping elements, thereby improving the phase stability while ensuring that the material has high fracture toughness and low thermal conductivity.
[0031] In the first aspect, an embodiment of the present application provides a thermal barrier ceramic material, which has the following composition: xA2O3·yBO2·zZrO2; wherein A is a trivalent rare earth metal ion; B is a tetravalent rare earth metal ion; the value range of x is 5% to 8%; the value range of y is 0% to 70%; 2x+y+z=1; the thermal barrier ceramic material includes a cubic phase structure.
[0032] In the embodiment of the present application, the thermal barrier ceramic material is based on ZrO2. By adjusting the total amount and type of rare earth doping elements, the thermal barrier ceramic material has a stable cubic phase and a partial cubic phase, which improves the phase stability while ensuring that the material has high fracture toughness and low thermal conductivity.
[0033] Among them, based on the total amount of material as 100%, the doping amount of trivalent rare earth metal ion oxide A2O3 in the thermal barrier ceramic material is 5%-8%, so that the thermal barrier ceramic material is mainly cubic phase, while improving the phase stability, ensuring that the material has high fracture toughness and low thermal conductivity, the doping amount of tetravalent rare earth metal ion B is 0%-70%, the tetravalent rare earth metal ion B and the oxide composed of it may or may not exist, when the tetravalent rare earth metal ion exists, the formed BO2 is similar to the ZrO2 lattice structure, which can further improve the phase stability.
[0034] The fracture toughness of the thermal barrier ceramic material in the embodiment of the present application is increased by 40% or more compared with new thermal protection materials such as rare earth zirconate ceramics; the thermal barrier ceramic material in the present application is calcined at 1400°C for 100 hours, and the monoclinic phase content is less than 3 mol%, indicating good phase stability.
[0035] The embodiments of the present application do not limit the aggregation state of the thermal barrier ceramic material, for example, it can be in block or powder form. The thermal barrier ceramic material of the embodiments of the present application can be used to prepare accessories of scramjet engines, aerospace engines, high-temperature gas turbines, etc. or used as a coating for accessories.
[0036] Exemplarily, the doping amount of the trivalent rare earth metal ion oxide A2O3 is 5%, 5.2%, 5.4%, 5.6%, 5.8%, 6%, 6.2%, 6.4%, 6.6%, 6.8%, 7%, 7.2%, 7.4%, 7.6%, 7.8% or 7.9%.
[0037] Exemplarily, the doping amount of the tetravalent rare earth metal ion B is 0%, 1%, 2%, 3%, 4%, 5%, 6%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65% or 70%.
[0038] In some embodiments, A includes Yb 3+ 、Lu 3+ Sc 3+ 、Nd 3+ 、Eu 3+ 、Sm 3+ , Gd 3+ 、Ho 3+ 、Dy 3+ , Y 3+ 、Tm 3+ , Er 3 + At least one of; B includes Ce 4+ and Hf 4+ At least one of .
[0039] The trivalent rare earth metal ion A can be one ion, two ions, or more than two ions. For example, the trivalent rare earth metal ion A is Yb 3+ , or the trivalent rare earth metal ion A is Lu 3+ , or the trivalent rare earth metal ion A is Yb 3+ He Lu 3+ .
[0040] Among them, Yb 3+ 、Lu 3+ Sc 3+ The ionic radius of Nd is relatively small, which can improve the phase stability of thermal barrier ceramic materials. 3+ 、Eu 3+ 、Sm 3+ , Gd 3+ 、Ho 3+ 、Dy 3+ , Y 3+ 、Tm 3+ , Er 3+ The ionic radius of the ions is relatively large, which can improve the sintering resistance of thermal barrier ceramic materials.
[0041] In the embodiment of the present application, the tetravalent rare earth metal ion B includes Ce 4+ and Hf 4+ At least one of Ce 4+ The ion radius is small, which has little effect on the phase structure of thermal barrier ceramic materials and can improve the stability performance. 4+It can improve the thermal expansion coefficient of thermal barrier ceramic materials and reduce thermal conductivity; the HfO2 crystal phase has a slow high-temperature growth rate, which can improve sintering resistance and fracture toughness. In addition, hafnium oxide HfO2 and ZrO2 are similar in chemistry and crystal structure, and HfO2 and ZrO2 are completely soluble in each other to form a solid solution, which helps phase stability.
[0042] The excellent sintering resistance described in this application means that the thermal barrier ceramic material obtained after sintering the ZrO2 green body has a higher porosity than the YSZ material.
[0043] In some embodiments, A includes a first trivalent rare earth metal ion and a second trivalent rare earth metal ion, based on the total amount of A, the content of the first trivalent rare earth metal ion is 60% to 100%, and the content of the second trivalent rare earth metal ion is 0% to 40%; the first trivalent rare earth metal ion includes Yb 3+ 、Lu 3+ Sc 3+ , Er 3+ At least one of the second trivalent rare earth metal ions including Nd 3+ 、Eu 3+ 、Sm 3+ , Gd 3+ 、Ho 3+ 、Dy 3+ , Y 3+ 、Tm 3+ , Er 3+ At least one of .
[0044] In the embodiments of the present application, trivalent rare earth oxides with relatively small ionic radius and relatively large ionic radius are mixed and doped, and the doping ratio of the two is regulated, so as to comprehensively improve the phase stability, thermodynamic properties and sintering resistance of the thermal barrier ceramic material.
[0045] In some embodiments, B includes 0-20 mol% Ce. 4+ and 0-50 mol% Hf 4+ .
[0046] In the present embodiment, Ce 4+ and Hf 4+ By mixed doping and regulating the doping ratio of the two, the phase stability, thermodynamic properties and sintering resistance of thermal barrier ceramic materials can be comprehensively improved.
[0047] In some embodiments, based on the total amount of the phase structure being 100%, the content of the cubic phase structure is 60%-100%.
[0048] In the embodiment of the present application, by adjusting the total amount and type of rare earth doping elements, the thermal barrier ceramic material has a stable cubic phase and a partial tetragonal phase, which improves the phase stability while ensuring that the material has high fracture toughness and excellent sintering resistance. The content of the cubic phase structure is 60%-100%.
[0049] In some embodiments, the thermal barrier ceramic material further includes a tetragonal phase and a monoclinic phase, and based on the total amount of the phase structure being 100%, the content of the monoclinic phase is 0-3%.
[0050] The thermal barrier ceramic material provided in the embodiment of the present application expands the zirconia-based material. By controlling the composition and proportion of the initial powder, it is ensured that the prepared material is mainly composed of cubic phase and a small amount of tetragonal phase. In addition, the monoclinic phase structure content of the thermal barrier ceramic material in the embodiment of the present application is less than 3 mol%, and has excellent phase stability.
[0051] In some embodiments, the fracture toughness K of the thermal barrier ceramic material IC ≥2.8Mpam 1 / 2 .
[0052] The thermal barrier ceramic material prepared in the embodiment of the present application has a high fracture toughness K IC , its value exceeds 2.8MPam 1 / 2 .
[0053] In a second aspect, an embodiment of the present application provides a method for preparing a thermal barrier ceramic material, which is used for the thermal barrier ceramic material of the present application, and is characterized by comprising:
[0054] Providing raw material components, including xA2O3, yBO2 and zZrO2, x is in the range of 5% to 8%; y is in the range of 0 to 70%; 2x+y+z=1; wherein A is a trivalent rare earth metal ion; B is a tetravalent rare earth metal ion;
[0055] mixing the raw material components to obtain a precursor mixture;
[0056] ball milling the precursor mixture and the solvent to obtain a mixed slurry;
[0057] The mixed slurry is subjected to solid-liquid separation to obtain a bulk material, and the bulk material is pre-calcined at least once to obtain a pre-fired thermal barrier ceramic material;
[0058] The pre-fired thermal barrier ceramic material is ball-milled, sieved, pre-pressed, and then calcined at 1350° C.-1600° C. for 6 h-10 h to obtain the thermal barrier ceramic material.
[0059] In the step of ball-milling the precursor mixture and the solvent to obtain a mixed slurry, zirconia balls and the precursor mixture can be ball-milled. For example, the ratio of the precursor mixture to the zirconia balls is between 1:20 and 1:10, and the ball-milling speed is between 200 and 300 rpm / min. The solvent can be alcohol or deionized water.
[0060] Before the step of mixing the raw material components to obtain the precursor mixture, the raw material components may be calcined to remove impurities such as water and carbon dioxide adsorbed by the raw material components. For example, the raw material components are calcined at 1100° C. for 1 h to 3 h.
[0061] In the step of obtaining a bulk material after solid-liquid separation of the mixed slurry, the bulk material can be obtained by filtering, and then the bulk material can be repeatedly ground, screened, and pre-calcined. The pre-calcination temperature is 1100°C-1250°C, and the time is 3h-10h. Through pre-calcination, the pre-fired thermal barrier ceramic material can have cubic phase and partial tetragonal phase products.
[0062] The step of ball-milling and sieving the pre-fired thermal barrier ceramic material and then pre-pressing and molding includes sieving the ball-milled powder, calcining at 1350-1500° C. for 1 h-3 h after spray granulation, and then sieving to select particles with a size of 30-110 microns. At this time, the particles with a size of 30-110 microns can be used for atmospheric plasma spraying. The pre-pressing molding can be processed by cold isostatic pressing.
[0063] By calcining at 1500℃-1600℃ for 6h-10h, a high-density thermal barrier coating material can be obtained, which can be used as EB-PVD target material or as a high-temperature structural material.
[0064] The embodiment of the present application uses rare earth-doped zirconia with excellent thermodynamic properties and excellent phase stability as the target material, controls the overall content of rare earth oxides to ensure that the target material is mainly tetragonal phase with a small amount of cubic phase, and synthesizes the target material through a simple solid phase reaction.
[0065] Specifically, the preparation method of the thermal barrier ceramic material in the embodiment of the present application is based on ZrO2. By adjusting the total amount and type of rare earth doping elements, the thermal barrier ceramic material has a stable cubic phase and a partial tetragonal phase. While improving the phase stability, it ensures that the material has high fracture toughness and excellent sintering resistance.
[0066] Among them, based on the total amount of material as 100%, the doping amount of trivalent rare earth metal ion oxide A2O3 in the thermal barrier ceramic material is 5%-8%, so that the thermal barrier ceramic material is mainly cubic phase, while improving the phase stability, ensuring that the material has high fracture toughness and low thermal conductivity, the doping amount of tetravalent rare earth metal ion B is 0%-70%, the tetravalent rare earth metal ion B and the oxide composed of it may or may not exist, when the tetravalent rare earth metal ion exists, the formed BO2 is similar to the ZrO2 lattice structure, which can further improve the phase stability.
[0067] The preparation method provided in the embodiment of the present application is simple, and the prepared thermal barrier ceramic material has a stable structure, excellent phase stability and is more resistant to sintering. After calcining at 1400° C. or above for 100 hours, it still has a stable composition and structure, and the monoclinic phase content is less than 3 mol%.
[0068] The fracture toughness of the thermal barrier ceramic material in the embodiment of the present application reaches 2.8MPam 1 / 2 above.
[0069] The thermal barrier ceramic material provided in the embodiment of the present application has better sintering resistance than YSZ by doping HfO2, and the porosity of the green sample after sintering under the same conditions is higher than that of traditional YSZ.
[0070] In some embodiments, A includes Yb 3+ 、Lu 3+ Sc 3+ 、Nd 3+ 、Eu 3+ 、Sm 3+ , Gd 3+ 、Ho 3+ 、Dy 3+ , Y 3+ 、Tm 3+ , Er 3 + At least one of .
[0071] In some embodiments, B includes Ce 4+ and Hf 4+ At least one of .
[0072] In a third aspect, an embodiment of the present application provides a thermal barrier coating material, which is formed by granulating and depositing the thermal barrier ceramic material of the first aspect of the present application.
[0073] Thermal barrier coating materials can be deposited by several techniques, including but not limited to thermal spraying (plasma spraying, flame spraying and HVOF spraying), sputtering and electron beam physical vapor deposition (EBPVD).
[0074] The thermal barrier coating material provided in the embodiment of the present application controls the composition and proportion of the initial powder to ensure that the prepared material is mainly composed of tetragonal phase and a small amount of cubic phase, and the monoclinic phase structure content of the thermal barrier ceramic material in the embodiment of the present application is less than 3 mol%, while improving the phase stability and ensuring that the material has high fracture toughness and excellent sintering resistance.
[0075] Example
[0076] The following examples describe the disclosure of the present application in more detail, and these examples are intended for illustrative purposes only, as it will be apparent to those skilled in the art that various modifications and variations may be made within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0077] Example 1
[0078] (a) The raw material components are A2O3, BO2 and ZrO2, which are calcined at 1100°C for 1-3 hours to remove adsorbed impurities such as water and carbon dioxide;
[0079] (b) weighing the dried A2O3, CeO2, HfO2 and ZrO2 in a specific ratio, the contents of which are shown in Table 1;
[0080] (c) The weighed powders are mixed by ball milling, wherein the ball milling medium is zirconia balls and alcohol, and the ball milling time is 8 hours.
[0081] (d) separating the slurry after ball milling, and grinding and sieving the obtained blocks,
[0082] Then calcined at 1100°C-1250°C for 8h;
[0083] (e) ball milling the obtained powder again for 7 hours, then sieving, and calcining at 1500° C.-1600° C. for 6-10 hours to obtain rare earth-doped ZrO2 powder;
[0084] (f) the powder after ball milling in step (e) is passed through a 200-300 mesh sieve, spray granulated, calcined at 1350-1500° C. for 1-3 hours, and then sieved to select particles with a size of 30-110 μm, which can be used for atmospheric plasma spraying;
[0085] (g) using a 15 mm diameter mold to pre-press the powder into a shape at a pressure of 5-10 kg; using cold isostatic pressing to hold the obtained green body at 200-300 MPa for 60-120 seconds;
[0086] (h) Finally, the sample is fired at 1500-1600°C for 6-10 hours to obtain a high-density rare earth-doped ZrO2 bulk sample, which can be used as an EB-PVD target or as a high-temperature structural material.
[0087] Embodiments 2 to 4
[0088] The preparation process is similar to that of Example 1, except that the doping ratio of the rare earth oxide is different. The components of the thermal barrier ceramic materials of Examples 2 to 4 are shown in Table 1.
[0089] Comparative Example 1-2
[0090] The preparation process is similar to that of Example 1, except that the doping ratio of the rare earth oxide is different. The components of the thermal barrier ceramic materials of Comparative Examples 1 to 2 are shown in Table 1.
[0091] Comparative Example 3
[0092] The preparation process is similar to that of Example 1, except that the tetravalent rare earth oxide in Comparative Example 3 is 40 molCe 4+ and 40 mol% Hf 4+ .
[0093] Comparative Example 4
[0094] The preparation process is similar to that of Example 1, except that in Comparative Example 3, the trivalent rare earth oxide is 10 mol La 3+ .
[0095] According to national standards, the fracture toughness of the sample was measured by the three-point bending method. The size of the sample was 20 mm × 4 mm × 2 mm, and the wire cutting technology was used to pre-cut the incision. The incision depth was about 2 mm. The fracture toughness of the sample was measured using a universal testing machine. A total of 5 samples were tested. The test results are shown in Table 1.
[0096] The molar percentages of cubic phase, tetragonal phase and monoclinic phase were obtained by testing the XRD spectrum of the sample and performing peak separation.
[0097] Table 1 Performance characterization and crystal structure of thermal barrier ceramic materials.
[0098]
[0099]
[0100] Figure 1 In the XRD patterns of the thermal barrier ceramic materials prepared in Examples 1 to 4 after calcination at 1400° C. for 100 hours, the materials are pure cubic phases without the presence of monoclinic phases.
[0101] Industrial Applicability
[0102] The multi-element rare earth doped zirconium oxide / hafnium oxide thermal barrier coating material of the present application not only has high melting point, excellent sintering resistance, high strength and other properties, but also has greatly improved fracture toughness compared with rare earth zirconate, and improved by 40% compared with pure rare earth zirconate, from ~2Mpam 1 / 2 Increased to ~2.8Mpam 1 / 2 Compared with traditional YSZ thermal barrier coating, it can be used for a long time at 1300℃. The thermal conductivity of this product is very low, less than 2.1Wm at 1000℃. -1 K -1 The above shows that the product has good practicality. In Comparative Example 3, due to excessive addition of CeO2, its phase composition changes, resulting in poor stability and mechanical properties.
[0103] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed in the present application, and these modifications or replacements should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.
Claims
1. A thermal barrier ceramic material, characterized in that: The thermal barrier ceramic material has the following composition: xA2O3·yBO2·zZrO2; Wherein, A is a trivalent rare earth metal ion; B is a tetravalent rare earth metal ion; The value range of x is 5% to 8%; the value range of y is 0% to 70%; 2x+y+z=1; the thermal barrier ceramic material includes a cubic phase structure.
2. The thermal barrier ceramic material according to claim 1, characterized in that: The A includes Yb 3+ 、Lu 3+ Sc 3+ 、Nd 3+ 、Eu 3+ 、Sm 3+ , Gd 3+ 、Ho 3+ 、Dy 3+ , Y 3+ 、Tm 3+ , Er 3+ At least one of; The B includes Ce 4+ and Hf 4+ At least one of .
3. The thermal barrier ceramic material according to claim 1 or 2, characterized in that: The A comprises a first type of trivalent rare earth metal ions and a second type of trivalent rare earth metal ions, based on the total amount of A, the content of the first type of trivalent rare earth metal ions is 60% to 100%, and the content of the second type of trivalent rare earth metal ions is 0% to 40%; The first type of trivalent rare earth metal ions includes Yb 3+ 、Lu 3+ Sc 3+ , Er 3+ At least one of the second trivalent rare earth metal ions including Nd 3+ 、Eu 3+ 、Sm 3+ , Gd 3+ 、Ho 3+ 、Dy 3+ , Y 3+ 、Tm 3+ At least one of .
4. The thermal barrier ceramic material according to claim 1 or 2, characterized in that: The B includes 0-20 mol% Ce 4+ and 0-50 mol% Hf 4+ .
5. The thermal barrier ceramic material according to claim 1, characterized in that: Based on the total amount of the phase structure being 100%, the content of the cubic phase structure is 60%-100%.
6. The thermal barrier ceramic material according to claim 1 or 5, characterized in that: The thermal barrier ceramic material also includes a tetragonal phase and a monoclinic phase. Taking the total amount of the phase structure as 100%, the content of the monoclinic phase is 0-3%.
7. The thermal barrier ceramic material according to claim 1, characterized in that: The fracture toughness K of the thermal barrier ceramic material IC ≥2.8Mpam 1 / 2 .
8. A method for preparing a thermal barrier ceramic material, used for preparing the thermal barrier ceramic material according to any one of claims 1 to 7, characterized in that: include: Providing raw material components, including xA2O3, yBO2 and zZrO2, x is in the range of 5% to 8%; y is in the range of 0 to 70%; 2x+y+z=1; wherein A is a trivalent rare earth metal ion; B is a tetravalent rare earth metal ion; mixing the raw material components to obtain a precursor mixture; ball-milling the precursor mixture and the solvent to obtain a mixed slurry; The mixed slurry is subjected to solid-liquid separation to obtain a block material, and the block material is pre-calcined at least once to obtain a pre-fired thermal barrier ceramic material; The pre-fired thermal barrier ceramic material is ball-milled, sieved, pre-pressed, and then calcined at 1350° C.-1600° C. for 6 h-10 h to obtain the thermal barrier ceramic material.
9. The method for preparing a thermal barrier ceramic material according to claim 8, characterized in that: A includes Yb 3+ 、Lu 3+ Sc 3+ 、Nd 3+ 、Eu 3+ 、Sm 3+ , Gd 3+ 、Ho 3+ 、Dy 3+ , Y 3+ 、Tm 3+ , Er 3+ At least one of; and / or, B includes Ce 4+ and Hf 4+ At least one of .
10. A thermal barrier coating material, characterized in that: The thermal barrier ceramic material according to any one of claims 1 to 7 is formed by granulating and spraying.